Deskripsi Electronic Word of Mouth dan Minat Beli Teh Cascara Netisane di Marketplace - Syifa, Puspa Dewi; Supyandi, Dika (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Netisane is a brand of herbal drink made from cascara. Netisane's most frequent promotions are through social media Instagram and marketplaces Shopee and Tokopedia. However, sales on the marketplace are lower compared to other marketing channels. This research aims to obtain a description of electronic word of mouth (e-WOM) and interest in buying Netisane cascara tea in the marketplace. The design in this research is descriptive quantitative with online survey techniques. Data collection was carried out using a questionnaire in the form of a Google form which was distributed via direct message Instagram. The population is combined viewers of the Instagram story content "Our Customer Review" which was uploaded 5 times on Netisane Instagram (netisane.co). The sample consisted of 72 respondents who were determined by applying the Yamane formula. The research results show that the intensity of uploads, the number of positive reviews, the absence of negative reviews and the informativeness and credibility of the research content are still lacking so they have not been able to generate buying interest among respondents.